Co-warm B2 - Zahar, Mohd Muzaffar; Joseph, Lavania Patricia; Mohd Zamri, Nadzir; Rosli, Siti Nursyarafana (Penerbit UTHM, 2020)
In this 21st century is where are the technologies are in advance technological development especially in electrics and electronics. Most of the vending machine can cool and warm the drinks separately. In personal used, the consumers need to buy two different products in cooling and warming the beverages. Practically, this contributes to the high-cost lifestyle and not user-friendly. This is more troubling if there are going for a travel or doing outdoor activities. Based on the current practical and applied technology in electronic device now, the power source of this proposed product uses the USB connection as its main source. Therefore, the target of this project to deliver the portable electronic device can be achieved.